2018
DOI: 10.1002/jsde.12201
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Sulfobetaine Gemini Surfactants with Hydroxyls and Their Effects on Surface‐Active Properties

Abstract: Sulfobetaine gemini surfactants, bis{[(N‐methyl‐N‐(3‐alkoxy‐2‐hydroxyl) propyl‐N‐(2‐hydroxyl‐3‐sulfonic acid sodium) propyl] methylene} ammonium chlorides (n = 10, 12, 14), were synthesized by etherification, ring‐opening reaction, and quaternization with epichlorohydrin, linear‐saturated alcohol, N,N′‐dimethylethylenediamine, and 3‐chloro‐2‐hydroxypropane sulfonic acid sodium as main raw materials. The structures of the sulfobetaine gemini surfactants with hydroxyls were characterized using Fourier transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The excellent comprehensive properties of sulfobetaine surfactants have attracted increasing research attention. At present, sulfobetaine surfactants are used in the chemical industry and tertiary oil recovery (Zhou et al, 2018). In the chemical industry, the most commonly used sulfobetaine surfactants are dodecyl hydroxysulfonyl betaine and octadecyl hydroxy‐sulfonyl betaine.…”
Section: Overview Of Sulfobetaine Surfactantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The excellent comprehensive properties of sulfobetaine surfactants have attracted increasing research attention. At present, sulfobetaine surfactants are used in the chemical industry and tertiary oil recovery (Zhou et al, 2018). In the chemical industry, the most commonly used sulfobetaine surfactants are dodecyl hydroxysulfonyl betaine and octadecyl hydroxy‐sulfonyl betaine.…”
Section: Overview Of Sulfobetaine Surfactantsmentioning
confidence: 99%
“…The sulfonic acid group and internal salt structure of sulfobetaine surfactant determine its stable properties, good temperature and salt tolerance, so it is expected to be used in oil displacement at high‐temperature and high‐salinity reservoirs (Zhou et al, 2017; Zhou, Bu, et al, 2018; Zhou, Chen, et al, 2018; Zhou, Liang, & Jia, 2018; Zhou, Zhang, et al, 2018). At the same time, sulfobetaine surfactants have excellent compatibility which can greatly reduce the chromatographic separation effect (the increase in interfacial tension value is due to the mismatch of polymer and surfactant concentration because of the difference of formation rock adsorption) when it is mixed with nonionic surfactants and/or polymers (Guo et al, 2018; Jiang et al, 2014; Kamal et al, 2016).…”
Section: Synthesis Of Sulfobetaine Surfactantmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the chemical structures of betaine surfactants are a crucial part in determining their physicochemical properties and even their application fields. To obtain comprehensive understanding of betaine surfactants, many studies have been carried out to synthesize novel kinds of betaine surfactants. Most studies have concentrated on investigating the effect of hydrophobic moieties modifications, the hydrocarbon chain length, and the types of hydrophilic headgroups , on physicochemical properties. For example, Kelleppan et al synthesized five long-chain amidopropyl betaines with C18 tailgroups and found that different degrees of unsaturation and branching significantly affect aggregation structures.…”
Section: Introductionmentioning
confidence: 99%